2003
DOI: 10.1038/sj.cr.7290148
|View full text |Cite
|
Sign up to set email alerts
|

Ohmefentanyl stereoisomers induce changes of CREB phosphorylation in hippocampus of mice in conditioned place preference paradigm

Abstract: The present study was designed to determine the changes of phosphorylation of cAMP-response element binding protein (CREB) in hippocampus induced by ohmefentanyl stereoisomers (F9202 and F9204) in conditioned place preference (CPP) paradigm. The results showed that mice receiving F9202 and F9204 displayed obvious CPP. They could all significantly stimulate CREB phosphorylation and maintained for a long time without affecting total CREB protein levels. The effect of F9204 was similar to morphine which effect wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…(1999a) reported CPP for ketamine (1, 3, 10 mg/kg ip) and dizocilpine (0.1, 0.2 mg/kg ip). Gao et al . (2003) also found that ketamine (10 mg/kg ip) produced a significant CPP, and a ketamine‐induced CPP (at 3 and 10 mg/kg ip, but not 1 mg/kg ip) was also reported by Suzuki et al .…”
Section: Studies Using Systemic Drug Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1999a) reported CPP for ketamine (1, 3, 10 mg/kg ip) and dizocilpine (0.1, 0.2 mg/kg ip). Gao et al . (2003) also found that ketamine (10 mg/kg ip) produced a significant CPP, and a ketamine‐induced CPP (at 3 and 10 mg/kg ip, but not 1 mg/kg ip) was also reported by Suzuki et al .…”
Section: Studies Using Systemic Drug Treatmentsmentioning
confidence: 99%
“…The development of CPP induced by morphine (10 mg/kg sc) and of two stereoisomers of ohmefentanyl, F9202 (18 µg/kg sc) and F9204 (2.5 µg/kg sc), was suppressed by ketamine (10 mg/kg ip) (Gao et al . 2003).…”
Section: Studies Using Systemic Drug Treatmentsmentioning
confidence: 99%
“…They are accompanied by alterations in neural plasticity at glutamate synapses. CREB, a transcription factor in particular has been implicated in opiates addiction (Nestler, 2001) and CPP (Gao et al, 2003). This result suggests that CREB may play an important role in the development of morphine-induced CPP.…”
Section: Introductionmentioning
confidence: 54%
“…Furthermore, we have previously reported that c-fos expression was increased in the parietal cortex, piriform cortex, striatum, nucleus accumbens, and hippocampus of the mouse brain, which produced morphine-induced CPP (Lee et al, 2003). A transcription factor, CREB, in particular has been implicated in opiates addiction (Nestler, 2001) and CPP (Gao et al, 2003) because its activation was a consequence of upregulation of the cAMP pathway, one of the well established adaptations to drug abuse (Hyman, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that ketamine suppresses not only the morphine-induced phosphorylation of CREB, but also the residue preference (10). A sub-anaesthetic dose of…”
Section: Introductionmentioning
confidence: 95%